Nadzieja na wojnę zwyciężającą pokój. Myśl rosyjska w latach 1914–1918 - Jedliński, Marek (Humaniora. Czasopismo Internetowe, 2024)
The article analyzes the self interpretative views of Russian thinkers on the Great War. Philosophers, historians and publicists unanimously assessed the armed conflict of 1914–1918 as a great change from the state of peace understood as apathy. The war was supposed to give hope for a positive transformation of Russia. According to philosophers, the conflict between the Orthodox East and the West was to lead to a renewal of the European spirit. The war was to destroy the foundations of Western thinking: rationalism, atheism, nihilism, militarism, capitalism and bourgeoisism. The German Empire for the Russians was the embodiment of these features of Modernity. The mission of the East was to be the religious revival of Europe, the liberation of the Slavs and the conquest of Constantinople.